COVID-19 and the risk of CNS demyelinating diseases: A systematic review - Lotan, Itay; Nishiyama, Shuhei; Manzano, Giovanna S.; Lydston, Melissa; Levy, Michael (Frontiers in Neurology, 2022)
Background Viral infections are a proposed possible cause of inflammatory central nervous system (CNS) demyelinating diseases, including multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein antibody -associated disease (MOGAD). During the past two years, CNS demyelinating events associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have been reported, but causality is unclear. Objective To investigate the relationship between CNS demyelinating disease development with antecedent and/or concurrent SARS-CoV-2 infection. Methods A systematic literature review of all publications describing either a new disease onset or relapse of CNS demyelinating diseases (MS, NMOSD, MOGAD) in association with SARS-CoV-2 infection was performed utilizing PRISMA guidelines. Descriptive statistics were used for data analysis, using a case analysis approach. Results Sixty-eight articles met inclusion criteria for the study. Most of the reported cases of NMOSD (n=13., 72.2% of reported cases) and MOGAD (n=27, 96.5% of reported cases) were of new disease onset, presenting with typical clinical and radiographic features of these conditions, respectively. In contrast, reported MS cases varied amongst newly diagnosed cases (n=10, 10.5% of reported cases), relapses (n=63, 66.4%) and pseudo-relapses (n=22, 23.2%). Median duration between COVID-19 infection and demyelinating event onset was11.5 days (range 0-90 days) in NMOSD, 6 days (range -7-+45 days) in MOGAD, and 13.5 days (range -21-+180 days) in MS. Most cases received high-dose corticosteroids with a good clinical outcome. Conclusions Based upon available literature, the rate of CNS demyelinating events occurring in the setting of preceding or concurrent SARS-CoV-2 infection is relatively low considering the prevalence of SARS-CoV-2 infection. The clinical outcomes of new-onset or relapsing MS, NMOSD or MOGAD associated with antecedent or concurrent infection were mostly favorable. Larger prospective epidemiological studies are needed to better delineate the impact of COVID-19 on CNS demyelinating diseases.